(untitled) (The Review of Diabetic Studies, 2023)
Type 2 diabetes and obesity are associated with systemic inflammation, generalized enlargement of fat depots, and uncontrolled release of fatty acids (FA) into the circulation. These features support the occurrence of cardiac adiposity, which is characterized by an increase in intramyocardial triglyceride content and an enlargement of the volume of fat surrounding the heart and vessels. Both events may initially serve as protective mechanisms to portion energy, but their excessive expansion can lead to myocardial damage and heart disease. FA overload promotes FA oxidation and the accumulation of triglycerides and metabolic intermediates, which can impair calcium signaling, β-oxidation, and glucose utilization. This leads to damaged mitochondrial function and increased production of reactive oxygen species, proapoptotic, and inflammatory molecules, and finally to myocardial inflammation and dysfunction. Triglyceride accumulation is associated with left ventricular hypertrophy and dysfunction. The enlargement of epicardial fat in patients with metabolic disorders, and coronary artery disease, is associated with the release of proinflammatory and proatherogenic cytokines to the subtending tissues. In this review, we examine the evidence supporting a causal relationship linking FA overload and cardiac dysfunction. Also, we disentangle the separate roles of FA oxidation and triglyceride accumulation in causing cardiac damage. Finally, we focus on the mechanisms of inflammation development in the fatty heart, before summarizing the available evidence in humans. Current literature confirms the dual (protective and detrimental) role of cardiac fat, and suggests prospective studies to establish the pathogenetic (when and how) and possible prognostic value of this potential biomarker in humans.